Workshop on scientific journal writing for school counselor in Pamekasan - Khairul Bariyyah; Laily Tiarani Soejanto (Jurnal Aplikasi IPTEK Indonesia, 2019)
Counselors as an educator qualification are required to continuously improve and develop academic qualifications and competencies. Professional development is carried out with a variety of things including writing scientific papers. This activity is conducted to provide training of school counselors to write the results of research that has been done, specifically with regard to making scientific articles that are ready to be submitted in reputable national and international journals. The subjects of this service are all Pamekasan school counselors. The method of implementing scientific article writing training activities for Pamekasan counselors is carried out through 3 stages, namely problem identification, implementation and evaluation. Data collection by qualitatively using analysis of interview results and observations of the participants in the activity. Training results show, after participating in this training activity, school counselors in Pamekasan have gained insight, knowledge and skills about writing scientific articles. This training has helped alleviate the workload of school counselors, especially related to scientific publication obligations